The Effect of Acupuncture Rejuvenation Combination of Gua Sha on The Smile Line Area in Mothers at RT 15 Rss. Sriwijaya Mothers South Sumatera - Putri, Arsy Amalia; Kusumawati, Heni Nur; Purwanto, Purwanto (Indonesian Journal of Acupuncture, 2024)
Wrinkles are formed due to the progressive aging process. Acupuncture therapy and a combination of gua sha in reducing the scale of facial wrinkles in the smile line area in mothers at Rss. Sriwijaya Sekarjaya Baturaja Timur Ogan Komering Ulu South Sumatera. This study used a Quasi-experimental research design with a two-group pre-test and post-test design and a purposive sampling technique with a sample size of 40 subjects. The group division consisted of 20 individuals for group 1 and 20 individuals for group 2. The result of the Wilcoxon test for acupuncture rejuvenation combination gua sha produced Asymp.Sig (2-tailed) ρ= 0,000 (ρ<0,005), and for local area combination gua sha produced Asymp.Sig (2- tailed) ρ = 0,001 (ρ<0,005). So it can be concluded that Ho rejected and Ha accepted, the acupuncture rejuvenation combination gua sha or local area acupuncture combination gua sha affects reducing the scale of wrinkles in the smile line.